2015
DOI: 10.1016/j.cej.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Matching of kinetics of CaCO3 decomposition and CuO reduction with CH4 in Ca–Cu chemical looping

Abstract: Ca-Cu chemical looping (CaL-CLC) based on calcium looping is a novel and promising process for CO 2 capture. The concept utilizes the heat released from the exothermic reduction of CuO to support the endothermic regeneration of CaO-based sorbents. Therefore, it is important for the two major reactions to have matching kinetics. This work assesses kinetics of the two reactions in a calciner under the conditions of interest for CaL-CLC. The reaction rates of the decomposition of CaCO 3 and reduction of CuO-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…A wide range of oxygen carriers has been proposed and tested by numerous researchers, as summarized elsewhere . In recent years a new process, integrated chemical looping combustion and calcium looping combustion, has been proposed . In this process, the use of CuO/CaO composites is suggested to provide two functions: transporting oxygen and capturing CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of oxygen carriers has been proposed and tested by numerous researchers, as summarized elsewhere . In recent years a new process, integrated chemical looping combustion and calcium looping combustion, has been proposed . In this process, the use of CuO/CaO composites is suggested to provide two functions: transporting oxygen and capturing CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of a solid fuel in a CLC scenario is possible, but natural gas has been chosen to avoid the presence of sulfur and ash because both affect the sorbent performance negatively . The reduction of copper oxide by methane in composite CaL–CLC pellets has also been investigated by multiple authors and fast reaction kinetics were observed; this was also positive for the process because it favored the complete reduction of copper, and thus, the complete release of the required heat for calcination.…”
Section: Computational Detailsmentioning
confidence: 99%
“…This process has previously been simulated for steam–methane reforming in a fixed‐bed configuration . Although fixed beds are easier to operate, fluidized‐bed reactors were chosen in this work due to the mitigated risk of hot spots and the continuous need for fresh sorbent addition. Moreover, the operation of fluidized beds generates a continuous feed of CO 2 to the compression train, whereas fixed beds would require the installation of multiple units to achieve such an operation.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature has been published in recent years about the application of the CLC concept at different pilot scales (Lyngfelt and Thunman, 2005;Linderholm et al, 2008;Forero et al, 2009;Kolbitsch et al, 2010;Lyngfelt, 2011;Fan et al, 2012). The use of a CueCuO chemical loop to carry out the calcination of CaCO3 on the basis of the unmixed combustion process (Lyon and Cole, 2000) has been also recently proposed, showing promising results in terms of low costs and high energy efficiency (Abanades et al, 2010;Kierzkoska and Müller, 2012;Martínez et al, 2014, Qin et al, 2015. Most CLC configurations consist of interconnected fluidized-bed reactors, which facilitate the transport of the oxidized carrier to the fuel reactor and its subsequent regeneration in the air reactor (Lyngfelt et al, 2001;Ishida et al, 2002).…”
Section: Introductionmentioning
confidence: 99%